Investigating the multidimensionality of informal learning: Validation of a short measure for white-collar workers - Julian Decius; Michael Knappstein; Niclas Schaper; Andreas Seifert (Human Resource Development Quarterly, 2021)
The challenges resulting from increasing digitalization and globalization require flexible continuing education for white-collar workers. Especially informal learning becomes increasingly important in the modern workplace. Practitioners want to promote informal learning among employees, researchers want to unveil conducive contextual conditions for informal learning, but they lack an appropriate, validated measure. Based on the octagon model of informal workplace learning (Decius et al., Human Resource Development Quarterly, 2019, 30, 495–535) and an existing 24-item scale for blue-collar workers, we present a short version of eight items for use among white-collar workers. Using three independent samples of 695, 500, and 3134 German employees, we show that the second-order factor structure—following the multidimensional octagon model—has a better fit compared with a model in which all items load on a single factor. The short scale is strongly correlated with the original full scale. The scale's reliability is satisfying (α~=~0.76/0.77/0.85; ω~=~0.78/0.78/0.86), considering the heterogeneous conceptual nature of informal learning. Regarding criterion validity, we found theoretically expected correlations with job demands, job autonomy, knowledge/skill acquisition, age, and self-directed learning orientation. Furthermore, the scale reveals measurement invariance across sociodemographic characteristics of gender and educational background. We also discuss implications for research and practice of the new informal learning measure among white-collar workers.
Keywords: 650; informal workplace learning; measure; short scale; validation; white-collar workers